Prevalence of HDV infection in people living with HIV: Data from a multicenter Italian cohort - Nicolini, Laura Ambra; Menzaghi, Barbara; Ricci, Elena; Pontali, Emanuele; Cenderello, Giovanni; Orofino, Giancarlo; Cascio, Antonio; Pellicanò, Giovanni Francesco; Valsecchi, Laura; Molteni, Chiara; Vichi, Francesca; Bonfanti, Paolo; et al. (Frontiers in Medicine, 2023)
Objectives The development of novel antiviral agents active against Hepatitis Delta Virus (HDV) might change the natural history of chronic infection, reducing the risk for end-stage liver disease. People living with HIV (PWH) are at risk for bloodborne pathogens infection, but limited data on epidemiology of HDV infection is available in this setting. The aim of this study was to investigate HDV prevalence and attitude towards HDV testing and treatment in infectious diseases centres. Methods A cross sectional survey was performed among centres participating in the CISAI (Coordinamento Italiano per lo Studio dell’Allergia in Infezione da HIV) Group. The survey addressed anti-HDV prevalence and HDV-RNA detectability rates in PWH as well as perceived obstacles to treatment. Results Overall, responses from ten sites were collected. Among participating centres, 316 PWH with HBV chronic infection are currently followed. Of them, 15.2% had positive anti-HDV antibodies, while 13.9% were not tested yet. Overall, 17% of anti-HDV positive PWH tested at least once for HDV-RNA had active HDV infection, and 71% of them had advanced liver disease. Most infectious diseases centres intended to treat locally HDV infection with upcoming anti-HDV drugs, but some concerns exist regarding treatment schedule. Discussion HDV testing need to be implemented in PWH. At present, few patients followed in the CISAI centres seem to be candidate to receive new direct active anti-HDV agents, but repeated HDV-RNA measures could change this proportion.